Wanprestasi Dalam Perjanjian Jual Beli Khususnya Yang Disebabkan Adanya Cacat Tersembunyi - Aris Priyadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
The main obligation of the seller in the sale and purchase agreement is to give up property rights over the object being traded and to bear enjoyment over the object and to bear any hidden defects. In Article 1504 of the Civil Code, namely the seller is obliged to bear hidden defects in the object being sold, which makes the object unable to use the intended use, or thereby reduces the use of it, so that if the buyer finds out about the defect, he will absolutely not buy the item, or will not buy it other than at a lower price. However, determining the size of the existence of a hidden defect in each person will be different, there may be someone who can accept the object he bought, even though according to the opinion of other buyers the object has hidden defects. The existence of hidden defects in the objects purchased can result in losses to the buyer because they do not get the object as expected in accordance with what has been previously agreed between the seller and the buyer, and will have legal consequences for the parties. From these descriptions, it encourages the author to write about a study of hidden defects in the agreement in the sale and purchase of movable objects. The research approach method used is juridical normative, while the research specification used is descriptive analysis.